Immobilization-Enhanced Eradication of Bacterial Biofilms and in situ Antimicrobial Coating of Implant Material Surface – an in vitro Study - Tran HA (Dove Medical Press, 2019)
Hien A Tran,1–4 Phong A Tran1–4 1School of Chemistry, Physics and Mechanical Engineering, Faculty of Science and Engineering, Queensland University of Technology (QUT), Brisbane, Queensland, Australia; 2Interface Science and Materials Engineering (ISME) Group, QUT, Brisbane, Queensland, Australia; 3Centre in Regenerative Medicine, QUT, Brisbane, Queensland, Australia; 4Institute of Health and Biomedical Innovation, Kelvin Grove, Queensland, AustraliaCorrespondence: Phong A Tran Tel +61 7 3138 6452Email phong.tran@qut.edu.auPurpose: The aim of this study was to investigate a new method of in situ biofilm treatment for infected prostheses that remove bacterial biofilm and prevent reinfection through the use of an immobilizing agent in combination with the actions of biofilm-lysing enzymes and bactericidal antimicrobials.Methods: We investigated the combination of self-immobilization chemistry of dopamine with a biofilm-lysing enzyme, α-amylase (Am), and an antimicrobial agent, silver nitrate (Ag), to treat model Staphylococcus aureus (S. aureus) biofilms formed on titanium. The efficacy of biofilm removal and bacterial treatment was analyzed by crystal violet, colony-forming unit assays, confocal laser scanning microscopy, and scanning electron microscopy (SEM). To confirm the in situ coating of the titanium surface with antimicrobial Ag as a strategy to prevent bacterial recolonization, SEM in secondary electron mode (SE), backscatter electron mode, (BSE) and energy-dispersive spectroscopy (EDX) were used. The antimicrobial activity of the coated surface was evaluated by optical density measurement and colony-forming unit assays.Results: Polydopamine (PDA)-assisted treatment showed approximately a 2 log reduction in recoverable CFU and a 15% increase in biofilm removal efficacy compared to treatments that had only Am or Ag. More importantly, PDA-assisted treatment was found to immobilize Ag on the surface after the treatment, rendering them resistant to bacterial recolonization.Conclusion: Our in vitro findings suggested that this PDA-assisted treatment and the surface immobilization-enhanced treatment concept could be promising in the development of advanced treatment for implant retention surgery for an infected prosthesis.Keywords: bacterial biofilm, in situ treatment, implants, antimicrobial, coatings